Answer:
[tex]f^{-1}(x)=\frac{x}{6}+\frac{2}{3}[/tex]
Step-by-step explanation:
Given function.
[tex]f(x)=6x-4[/tex]
To find the inverse function [tex]f^{-1}(x)[/tex]
Step 1:
Replace [tex]f(x)[/tex] with[tex]y[/tex] in the function.
[tex]y=6x-4[/tex]
Step 2:
Interchange [tex]y[/tex] with [tex]x[/tex] in the equation.
[tex]x=6y-4[/tex]
Step 3:
Solve for [tex]y[/tex].
We have [tex]x=6y-4[/tex]
Adding 4 to both sides,
[tex]x+4=6y-4+4[/tex]
[tex]x+4=6y[/tex]
Dividing each term by 6 to isolate [tex]y[/tex]
[tex]\frac{x}{6}+\frac{4}{6}=\frac{6y}{6}[/tex]
[tex]\frac{x}{6}+\frac{4}{6}=y[/tex]
Simplifying fractions by dividing the numerator and denominator by their GCF.
[tex]\frac{x}{6}+\frac{4\div 2}{6\div 2}=y[/tex]
[tex]\frac{x}{6}+\frac{2}{3}=y[/tex]
Thus the equation of [tex]y[/tex] is:
[tex]y=\frac{x}{6}+\frac{2}{3}[/tex]
Step 4:
Replace [tex]y[/tex] with [tex]f^{-1}(x)[/tex]
[tex]f^{-1}(x)=\frac{x}{6}+\frac{2}{3}[/tex] (Answer)
Thus, we have the inverse function